Pain After Preoperative Ultrasound Guided Hip Injections for Total Hip Arthroplasty: A Pilot Randomized Controlled Trial. (April 2023) - Holbert, S. Elliott; Fowler, Brook; West, Michaline; Morris, Jennifer; Turcotte, Justin; King, Paul
Introduction. Hip replacement is a frequently performed and highly successful treatment for patients with end stage osteoarthritis. Advances in technique and pain management have allowed for rapid mobilization and early discharge after surgery. We hypothesize that pre-incision intra-articular injection of local anesthetic with epinephrine under image guidance combined with post incision peri-articular injection (PAI) may be more effective than PAI alone. Methods. A prospective, randomized, controlled, comparative investigation at a single institution of 41 patients undergoing THA who received standard 30 mL post-arthrotomy, PAI of ropivacaine with epinephrine under direct visualization after prosthesis implantation before closure or an equivalent dose divided into a 10 mL pre-incision, ultrasound guided intra-articular injection and a 20 mL post-arthrotomy PAI. Results. 42 patients were included in this study before its early conclusion with 22 patients in the treatment group and 20 in the control group. There were no significant differences in age, BMI or ASA scores. Additionally, there were no significant differences noted when comparing groups by postoperative outcome measures including OMME, EBL, OR time, PACU minutes, and first and last PACU pain score. Furthermore, there were no significant differences in the PROMs evaluated. Discussion. The addition of ultrasound guided pre-incision intra-articular injection to the standard PAI had no benefit when compared with standard PAI during a THA. Portable mobile phone based ultrasound devices provide a cost effective way to perform musculoskeletal blocks, and further studies on their use and comparative accuracy is warranted. A novel technique for confirmation of injection location is described.